K. I. Abramov’s contribution to the development of the methodology of library history: historical reconstruction - E. A. Pleshkevich (Библиосфера, 2020)
The article is devoted to the contribution of the famous Russian specialist in library science K. I. Abramov to the methodology of library history, the author of almost 340 publications, of which two-thirds are devoted to history. The importance of his contribution to the development of source studies, historiography, archeography, and library history is emphasized. Based on the principle of historicism and methods of structural analysis, the historical reconstruction of the formation and development of his methodological views was carried out. The external conditions of his formation as a historian are analyzed. It is noted that the formation took place in difficult socio-political conditions. The main conclusions are as follows. The methodological views of K. I. Abramov were based on the relying on archival material, striving to improve the scientific character of historical research, overcoming the desire to reduce research to a superficial presentation and commentary on certain Leninist positions. With his participation, Lenin and Krupskaya’s works on library science were collected and published. At the same time, his worldview was characterized by a dogmatic attitude to Marxism and its methodology, an unconditional adherence to the leading quote, and a non-critical attitude to the statements of the classics of Marxism-Leninism. The Marxist-Leninist doctrine of culture and the library heritage of Lenin and Krupskaya served as a theory in Abramov’s works; the dominance of historical and pedagogical research, which is characterized by following the official interpretation of certain events, simplified presentation of historical processes and events, unambiguity of author’s judgments and assessments, avoiding halftones, exalting achievements while concealing mistakes and failures.The analysis also showed that in the 1990s, under the influence of socio-political changes and rejection of Marxism-Leninism, Abramov revised his attitude to the history of Soviet library construction. He began to focus on the theory of democracy, in the context of which libraries were seen as a vehicle for democracy, and the leading role in library construction was given to the public library movement. He puts forward the concept of democratic library science, which was formed in the period between the February and October revolutions and was rejected by the Bolsheviks.The significance of this study is associated with the generalization of Abramov’s methodological heritage aimed at developing the positive aspects of his methodology, as well as overcoming methodologically incorrect judgments about the history of Soviet library construction.